Long-Read Sequencing – A Powerful Tool in Viral Transcriptome Research. Issue 7 (July 2019) - Boldogkői, Zsolt; Moldován, Norbert; Balázs, Zsolt; Snyder, Michael; Tombácz, Dóra
Abstract : Long-read sequencing (LRS) has become increasingly popular due to its strengths in de novo assembly and in resolving complex DNA regions as well as in determining full-length RNA molecules. Two important LRS technologies have been developed during the past few years, including single-molecule, real-time sequencing by Pacific Biosciences, and nanopore sequencing by Oxford Nanopore Technologies. Although current LRS methods produce lower coverage, and are more error prone than short-read sequencing, these methods continue to be superior in identifying transcript isoforms including multispliced RNAs and transcript-length variants as well as overlapping transcripts and alternative polycistronic RNA molecules. Viruses have small, compact genomes and therefore these organisms are ideal subjects for transcriptome analysis with the relatively low-throughput LRS techniques. Recent LRS studies have multiplied the number of previously known transcripts and have revealed complex networks of transcriptional overlaps in the examined viruses. Highlights: Long-read sequencing (LRS) has revolutionized genomics and transcriptomics. These third-generation approaches have a relatively low throughput compared to short-read sequencing, but they can solve problems that used to be a challenge for earlier techniques. The PacBio and ONT sequencing are able to read full-length transcripts and allow the direct study of base modifications on both DNA and RNA molecules. Nanopore technology is able to sequence RNA directly. LRS has revealed a much more complex viral transcriptome. Among other capabilities, these techniques allow the discrimination between multispliced transcript variants, RNA length isoforms, embedded RNAs, and polycistronic RNA molecules. The viral genomes express a highly complex pattern of transcriptional overlaps, the function of which continues to remain unknown.